Exploring the Use of E-Lumak in Teaching: Insights from Lecturers - Faridawati; Pebriani, Wa Ode; Syahriani, Ririn (Jurnal Genesis Indonesia, 2025)
This study explores lecturers' perceptions of E-Lumak, a digital teaching platform used at Universitas Muhammadiyah Kendari. Using a descriptive qualitative approach, three English Language Education lecturers were interviewed through semi-structured questions, providing in-depth insights. Thematic analysis of the data revealed that lecturers generally viewed E-Lumak positively. They highlighted several benefits, including improved pedagogy, easier management of the learning process, and greater flexibility and efficiency in teaching. However, challenges such as technical issues, time-consuming material preparation, and difficulties navigating certain features of the platform were also noted. Despite these challenges, the lecturers reported that the overall teaching and learning experience was not significantly hindered. This research emphasizes the need to integrate digital platforms like E-Lumak into educational settings, as they can enhance teaching effectiveness and improve the overall learning experience, despite certain obstacles.